Semiological Discourse Analysis of the Editorial Cartoons of International Newspapers on COVID-19 - Mutaz Mohammad Alkhresheh (Institute of Medico-legal Publications Pvt Ltd, 2020)
The present study aimed to find the hidden ideological approaches used by the newspaper editors in theportrayal of their cartoons in the respective newspapers. The target of this research was to achieve a broadspectrum comparison of semiotics as depicted in international newspapers as Dawn based in Pakistan andThe Economist based in Britain. The objectives of the research were achieved by dividing the study into twoparts. At first, the written parts of the cartoons were analyzed, and secondly, the semiotics was analyzed.An integrated framework of analysis was used and the researcher blended the CDA model by NormanFairclough and the semiological framework of Roland Barthes. The study revealed that Dawn presented thedomestic problems of the health care system. Further Dawn presented the severe attacks of Covid-19 andlocusts and the drastic effects of locusts on the agriculture-based economy. The Economist presented anAmerican cultural disorder of racism that has been part of its earlier history. The Economist also highlightedthe precarious state of Brazil and the inefficiency of the government to tackle the spread of Covid-19. It wasconcluded that the semiotics presented in the newspapers portrayed the situation related to Covid-19 andits long-lasting effects have been discussed in the context of culture and social practice. A comparison ofsemiotics was presented at the end of the study.